Recalibrating Judicial Oversight in Indonesia: The Binding Force of the Judicial Commission’s Recommendations - Violetta, Sukma; Saragih, Bintan R; Budianto, Agus (Journal of Cultural Analysis and Social Change, 2026)
This article examines the institutional challenges and reform imperatives of Indonesia’s Judicial Commission in enforcing judicial ethics and accountability within the framework of judicial independence. Despite its constitutional mandate under Article 24B of the 1945 Constitution, the Commission’s recommendations to the Supreme Court remain non-binding, resulting in weak enforcement and persistent institutional tension between oversight and independence. Through a comparative analysis of judicial councils in France and Italy, the paper highlights how binding disciplinary authority may strengthen judicial legitimacy without compromising autonomy. The study argues for amending Law on Judicial Commission to grant binding legal force to the Commission disciplinary decisions, supported by administrative implementation by the Supreme Court. Such reform would institutionalize ethical accountability, enhance public trust, and align Indonesia’s judicial governance with established international best practices.